Optimization of Ilmenite Conversion to High-Purity Titanium Dioxide (TiO₂) in the Ternary System TiO₂-Fe₂O₃-Na₂O - Listiawati, Listiawati; Astroha, Robie Wilson; Sunandar, Arman (IHSA Institute, 2025)
This research investigates the conversion of ilmenite (FeTiO₃) to titanium dioxide (TiO₂) in the ternary system TiO₂-Fe₂O₃-Na₂O, focusing on improving TiO₂ yield, purity, and quality for industrial applications. The study explores the effect of sodium oxide (Na₂O) as a flux to facilitate the removal of iron oxide (Fe₂O₃) impurities, which often degrade TiO₂'s optical and chemical properties. Through a series of experiments varying Na₂O concentrations and temperatures (900-1200°C), the research demonstrates that Na₂O enhances TiO₂ formation by promoting phase transitions and accelerating the separation of iron from titanium. Optimal conditions (5% Na₂O at 1100-1200°C) resulted in high-purity TiO₂ (up to 99%) with yields reaching 95%, while reducing iron oxide contamination. This study provides valuable insights into the reaction mechanisms and optimal parameters for producing high-quality TiO₂, with significant implications for its use in pigments, coatings, and advanced materials where purity and performance are critical. The findings contribute to more efficient, scalable methods for TiO₂ production from ilmenite, benefiting industries dependent on this essential material.